Magnesia carbon brick for quick change of converter bottom and preparation method of magnesia carbon brick

By quickly replacing magnesium carbon bricks with converter bottoms with gradient refractory materials, the problem of magnesium carbon bricks being easily damaged during smelting special steels in the prior art is solved, and the formation of stable slag-metal mushroom head structure and the extension of the life of magnesium carbon bricks are achieved.

CN119954498APending Publication Date: 2025-05-09SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510058369.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The magnesium carbon bricks are easily damaged when smelting special steel, resulting in a significant reduction in the age of the furnace. In the early stage of smelting, the smelting must be ordinary steel, which cannot effectively protect magnesium carbon bricks.

Method used

The converter furnace bottom using gradient refractory materials is quickly replaced with magnesium carbon bricks, which includes the reaction section, the middle section and the rear section. Through specific phase combinations and additives, a stable slag-metal mushroom head structure is formed to enhance corrosion resistance and high temperature strength.

Benefits of technology

The stable slag-metal mushroom head structure can be formed in the early stage of converter smelting, which significantly extends the life of magnesium-carbon bricks and allows the smelting of special steel in the early stage to maximize the number of special steel smelting furnaces.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a magnesia carbon brick for quick change of a converter bottom and a preparation method of the magnesia carbon brick. The magnesia carbon brick is a gradient refractory material and is divided into a reaction section, a middle section and a rear section. The method comprises the following steps: sequentially passing blocky fused magnesia, sintered magnesia, forsterite and calcium-containing magnesia through a jaw crusher, a roll crusher and a Raymond mill to obtain corresponding aggregate particles and matrix fine powder; the method comprises the following steps: uniformly mixing reaction section, middle section and rear end matrix fine powder in advance according to a formula; uniformly mixing the aggregate particles according to a reaction section formula, a middle section formula and a rear end formula, then adding a phenolic resin binding agent, uniformly stirring, then adding graphite, then adding uniformly premixed matrix fine powder, uniformly stirring, then transporting to a brick press, sequentially distributing materials, carrying out mechanical pressing, and carrying out heat treatment, so as to obtain the magnesia carbon brick for the converter bottom quick change. The magnesia carbon brick for quick change of the converter bottom can overcome the defects that the existing magnesia carbon brick for quick change of the converter bottom must be made of common steel in early smelting and the converter bottom magnesia carbon brick can be directly damaged by smelting special steel, and stabilizes and prolongs the service life of the converter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of refractory materials, and in particular to a magnesia carbon brick for quick replacement of a converter bottom and a preparation method thereof. Background Art

[0002] During the steelmaking process, the refractory materials at the bottom of the converter are easily damaged due to long-term exposure to high temperatures and erosion. The traditional replacement method requires the furnace to be stopped and cooled before replacement, which is not only time-consuming but also affects production efficiency. Therefore, the emergence of the converter bottom quick-change technology has achieved rapid replacement of the bottom refractory materials in the hot state of the converter, which is of great significance for improving steelmaking efficiency and reducing costs. In order to speed up the turnover rhythm of the converter used to smelt carbon steel, Shanxi Taigang Stainless Steel Co., Ltd. adopts the bottom quick-change mode, which shortens the time from one week to less than 3 days.

[0003] Although the quick change of the converter bottom shortens the masonry time, it also has strict requirements on the selection of steel grades for steelmaking. For example, in the first 35 furnaces or so, medium and high carbon steel grades (Q235B, Q195, etc.) must be smelted to form a slag-metal mushroom head with a stable structure, which covers the magnesia-carbon bricks at the bottom of the converter, protects the bottom of the converter, reduces the impact of molten steel and slag and smelting temperature fluctuations on the magnesia-carbon bricks at the bottom, avoids the impact of magnesia-carbon bricks on molten steel, and increases the life of magnesia-carbon bricks at the bottom of the converter.

[0004] The steel types smelted by Shanxi Taigang Stainless Steel Co., Ltd. are mainly special steels such as stainless steel and silicon steel, while ordinary steels such as Q235 account for a relatively low proportion. The smelting of a large amount of ordinary steels such as Q235 in the early stage will not only cause a waste of resources, but also increase costs and extend delivery time. The smelting of a small amount of ordinary steel in the early stage and then the smelting of special steel will cause large-scale damage to the magnesia carbon bricks at the bottom of the converter, and the furnace life will be directly reduced from about 8,000 furnaces to 5 furnaces. The reason is that the smelting of special steel causes the damage of the slag-metal mushroom head, the magnesia carbon bricks at the bottom of the furnace are in direct contact with the steel / slag, and the smelting temperature of special steel is relatively high, resulting in large-scale damage to the magnesia carbon bricks at the bottom of the furnace. In order to increase the furnace life and avoid the impact of special steel on the magnesia carbon bricks at the bottom of the converter in the early stage of smelting, it is necessary to develop a new magnesia carbon brick that can form a stable slag-metal mushroom head structure in the early stage of smelting to protect the magnesia carbon bricks at the bottom of the converter, while increasing the life and maximizing the number of special steel smelting furnaces.

[0005] At present, the patents of magnesia carbon bricks for converters are concentrated on the rest of the converter or the bottom of non-quick-change converters, such as the patent "Preparation process of magnesia carbon bricks for converter steel outlet (CN202311726437.9)", the patent "A low-carbon magnesia carbon brick for converter stainless steel production and its preparation process (CN202311025636.7)", etc. There are few patents related to magnesia carbon bricks for quick-change converter bottoms, such as the patent "A method for replacing converter bottom blowing seat bricks (CN201910483457)", which focuses on the replacement method rather than the magnesia carbon bricks themselves. However, there are no reports on magnesia carbon bricks for quick-change converter bottoms related to steel smelting.

[0006] The present invention aims to overcome the defects of the prior art and has the purpose of providing a magnesia-carbon brick for quick replacement of the converter bottom and a preparation method thereof, so as to overcome the defects that the magnesia-carbon brick for quick replacement of the converter bottom must be smelted with ordinary steel in the early stage, and the smelting of special steel will directly damage the magnesia-carbon brick for the converter bottom, thereby stabilizing and improving the service life of the converter. Summary of the invention

[0007] The purpose of the present invention is to provide a magnesia carbon brick for quick replacement of converter bottom and a preparation method thereof in view of the above problems.

[0008] The object of the present invention is achieved as follows: A magnesia carbon brick for quick change of converter bottom and its preparation method, comprising the following steps: Step 1: Preparation of aggregate: 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed by a jaw crusher in turn and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles; to maintain material balance, 10-70% of 1-3mm or 3-5mm are crushed into 0.1-1mm or 1-3mm by a double-roll crusher; the crushed particles are stored in corresponding silos according to the particle size; 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles; Step 2: Preparation of matrix fine powder: silo storage After 5-12 tons of particles in step one, stop storing, and then send the particles that have passed through the jaw crusher directly into the Raymond mill, and the powder is formed into a matrix fine powder with a particle size of less than 0.088 mm, namely, fused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, and calcium-containing magnesia fine powder, and stored in the corresponding silo; in actual production, step one and step two can be carried out simultaneously to shorten the preparation time of aggregate and matrix; step three: mixing and molding: the freight car transports the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer, the mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt; the magnesia-carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860±30 mm, divided into a reaction section of 260±10mm, a middle section of 350±10mm and a rear section of 350±10mm; reaction section: 3-5% of fused magnesia fine powder, 3-8% of sintered magnesia fine powder, 10-15% of calcium-containing magnesia fine powder and 4-8% of forsterite fine powder are transported to the Eirich mixer and mixed for 3-5 minutes, during which 0.1-1% of aluminum powder and 0.2-0.9% of silicon powder additives are manually added from the feeding port of the Eirich mixer. After uniform mixing, the reaction section matrix fine powder is obtained, and 1-3% of fused magnesia particles with a mass ratio of large, medium and small particles of 1:2:1, 4-7% of sintered magnesia particles with a mass ratio of large, medium and small particles of 1.2:2:0.8, and 30-45% of large, medium and small particles are added. The calcium-containing magnesium sand particles with a mass ratio of 1.1:2:0.9 and the forsterite particles with a mass ratio of large, medium and small particles of 15-25% and a mass ratio of 1.05:2:0.95 are transported to a planetary mixer and mixed for 3-5 minutes, and then 3.0-3.6% of a phenolic resin binder is added and stirred for 3-5 minutes, and then 14-18% of low-carbon graphite fine powder is manually added and mixed for 4-5 minutes, and finally the reaction stage matrix fine powder is added and mixed for 3-5 minutes to obtain a reaction stage mixture; middle stage: 6-20% of fused magnesium sand fine powder and 3-7% of sintered magnesium sand fine powder are transported to an Eirich mixer and mixed for 3-5 minutes, during which 0.5-1.5% of aluminum powder and 0.4-1.3% silicon powder additive is added, and the middle matrix fine powder is obtained after being mixed evenly; 50-60% fused magnesia particles with a mass ratio of large, medium and small particles of 1:2:1 and 10-15% sintered magnesia particles with a mass ratio of large, medium and small particles of 1.2:2:0.8 are transported to a planetary mixer and mixed for 3-5 minutes, and then 3.5-4.0% phenolic resin binder is added and stirred for 3-5 minutes, and then 11-13% high-purity graphite fine powder and 3 are added manually. -5% flake graphite particles are mixed for 4-5 minutes, and finally the middle stage matrix fine powder is added and mixed for 3-5 minutes to obtain a middle stage mixture; the back stage: 3-9% fused magnesia fine powder and 10-18% sintered magnesia fine powder are transported to the Eirich mixer and mixed for 3-5 minutes, during which 0.1-1.0% aluminum powder and 0.2-0.9% silicon powder additives are manually added from the Eirich mixer feeding port, and the back stage matrix fine powder is obtained after mixing evenly; 10-15% of fused magnesia particles with a mass ratio of large, medium and small particles of 1:2:1 and 50-60% of sintered magnesia particles with a mass ratio of large, medium and small particles of 1.2:2:0.8 are transported to a planetary mixer and mixed for 3-5 minutes, then 3.0-3.2% of phenolic resin binder is added and stirred for 3-5 minutes, and then 14-18% of high-purity graphite fine powder is manually added and mixed for 4-5 minutes, and finally the back-stage matrix fine powder is added and mixed for 3-5 minutes. min, and obtain the rear section mixture; the reaction section, middle section, and rear section mixtures are transported to the brick press by belts respectively, and the materials are laid in the order of 260±5mm for the reaction section, 350±5mm for the middle section, and 350±5mm for the rear section, and then pressurized at 30-50MPa for 5-10s and 150-200MPa for 5-10s, and then heat treated at 200-250℃ for 24-32h to obtain the magnesia carbon brick for quick change of converter bottom. .

[0009] The fused magnesia has MgO≥97%, SiO2≤0.6%, CaO≤1.5%, B2O3≤0.01%, particle size: 5-50mm; bulk density 3.45-3.53g / cm 3 , true porosity 0.5-2.5%, grain size 270-700μm; the sintered magnesia MgO≥95%, SiO2≤2.2%, CaO≤1.8%, particle size: 5-50mm, volume density 3.20-3.47g / cm 3 , true porosity 0.3-3.5%, grain size 10-200μm; the forsterite MgO+SiO2≥95%, SiO2≥40%, CaO≤1.0%, Al2O3≤1.0%, particle size 5-50mm, volume density 3.22-3.33g / cm 3The calcium-containing magnesia sand has MgO≥90%, CaO is 5-10%, ∑SiO2+Al2O3+Fe2O3≤3.0%, a particle size of 5-50mm, and a bulk density of 3.42-3.47g / cm 3 .

[0010] The production capacity of the jaw crusher is 250-350t / h, the finished product specification is 0-5mm, and the maximum feed particle size is 700mm; the production capacity of the double-roll crusher is 50-100t / h, the finished product specification is 0-3mm, and the maximum feed particle size is 60mm; the production capacity of the Raymond mill is 10-320t / d, the finished product specification is 0.015-0.088mm, and the maximum feed particle size is 30mm; the model of the Eirich mixer is RV24, and the speed is 0-1751r / min; the capacity of the planetary mixer is 800-1200kg, and it has a heating function.

[0011] The aluminum powder has Al≥98%, Fe≤0.5%, Si≤0.5%, Cu≤0.1%, and a particle size of 0.015-0.074 mm; the silicon powder has Si≥98%, and a particle size of 0.015-0.074 mm.

[0012] The phenolic resin is in liquid state, with a viscosity of 0.75-0.95 Pa·s at 25° C., a moisture content of 1.5-2.5%, a solid content of 75-80%, a residual carbon rate of 43-48%, a free phenol content of 10.0-12.0%, and a pH value of 6.5-7.5.

[0013] The low-carbon graphite fine powder has a fixed carbon content of 50-80%; the main components of the ash are SiO2, Al2O3 and Fe2O3, and the ∑SiO2+Al2O3+Fe2O3 in the ash is 82.9-88.6%, of which SiO2 accounts for 33-59%, and the particle size is 0.044-0.074mm.

[0014] The high-purity graphite fine powder has a fixed carbon content of ≥99.9% and a particle size of 0.074-0.1 mm.

[0015] The flake graphite particles have a fixed carbon content of ≥99.9% and a particle size of 1-3 mm.

[0016] The brick press is a friction brick press.

[0017] The magnesia-carbon brick for quick replacement of the converter bottom is a magnesia-carbon brick for quick replacement of the converter bottom prepared by the method for preparing magnesia-carbon brick for quick replacement of the converter bottom according to any one of claims 1 to 9.

[0018] The beneficial effects of the present invention are as follows: the magnesia-carbon brick for quick change of converter bottom prepared by the present invention is a gradient refractory material, and the reaction section is mainly composed of forsterite, periclase, calcite, and amorphous carbon. Due to its high SiO2 and low refractoriness (1710°C), forsterite is easy to react with converter slag. The presence of calcite provides a way for the slag to further erode periclase, and it is easy to form a slag-metal mushroom head structure. Due to the presence of many highly active sites, amorphous carbon makes it difficult for metal elements such as Fe to be oxidized, thereby enhancing the stability of the slag-metal mushroom head; the high ash content of low-carbon graphite also allows the refractory material to further fuse with the slag, which can promote the fusion of the slag-metal mushroom head more quickly. Therefore, through the interaction between the reaction section of the magnesia-carbon brick for quick change of converter bottom and the slag, a stable slag-metal mushroom head structure is formed within 5 furnaces in the initial stage of converter smelting.

[0019] The main phases of the middle section are large crystalline periclase and graphite of different particle sizes, which have excellent corrosion resistance. In the strong smelting environment of the converter, even under extreme conditions, the reaction section is completely slagified, which can provide a stable attachment site for the slag-metal mushroom head and maintain the stability of the slag-metal mushroom head structure; and it is not easily corroded by the converter slag. Due to the existence of the reaction section, the reaction section is easy to slag, which can effectively buffer most of the thermal stress and mechanical force; therefore, the middle section can use a large amount of granular graphite and large crystalline fused magnesia to fully enhance the corrosion resistance and less consider the high temperature strength. The TISCO converter is a top and bottom blown converter, and sometimes CO2 is used as the bottom blowing gas. Large crystalline magnesia, flake graphite and high-purity graphite have low reactivity and are not easy to react with CO2.

[0020] The main phases of the rear section are periclase and graphite. The periclase grains are small and the graphite particle size is low, so it has good high-temperature strength. According to actual use experience, when there is less high-carbon steel in the initial smelting, the fracture of the converter bottom is mostly located in the rear section; the rear section does not contact the slag, so the main fracture damage mode is mechanical spalling or thermal spalling. For this reason, small-grain sintered magnesia is used to increase the high-temperature strength, and high-purity magnesia is used to increase oxidation resistance, in order to increase the overall fracture toughness of the rear section.

[0021] According to the principle of the most densely packed particles, the proportions of large, medium and small particles of each aggregate are determined to reduce or even avoid the segregation of the mixture during transportation and pressing, thereby improving the overall performance of the magnesia carbon bricks.

[0022] Therefore, the magnesium carbon bricks for quick replacement of the converter bottom prepared by the present invention overcome the defects of the existing magnesium carbon bricks for quick replacement of the converter bottom that the initial smelting must be ordinary steel, and the smelting of special steel will directly damage the magnesium carbon bricks at the converter bottom, stably form slag-metal mushroom heads, stabilize and improve the service life of the converter. DETAILED DESCRIPTION

[0023] The technical solution adopted by the present invention is: the magnesia carbon brick for quick change of converter bottom and its preparation method, characterized in that the steps of the preparation method are: step 1 (aggregate preparation): 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles by a jaw crusher in turn; to ensure the balance of the material block surface, 10-70% 1-3mm or 3-5mm can be crushed into 0.1-1mm or 1-3mm by a double-roll crusher. The crushed particles are stored in the corresponding silo according to the particle size.

[0024] 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles.

[0025] Step 2 (preparation of matrix fine powder): After the silo stores 5-12 tons of the particles, stop storing. Next, the particles that have passed through the jaw crusher are directly sent to the Raymond mill to form the matrix fine powder (electrofused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, calcium-containing magnesia fine powder) with a particle size of less than 0.088 mm after powdering, and stored in the corresponding silo.

[0026] In actual production, step one and step two can be performed simultaneously to shorten the preparation time of aggregate and matrix.

[0027] Step 3 (mixing and molding): Use a computer to control the transport cart to transport the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer. The mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt.

[0028] The magnesia-carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860±30 mm, divided into a reaction section (260±10 mm), a middle section (350±10 mm) and a rear section (350±10 mm).

[0029] Reaction section: 3-5% of fused magnesia fine powder, 3-8% of sintered magnesia fine powder, 10-15% of calcium-containing magnesia fine powder, and 4-8% of forsterite fine powder are transported to the Eirich mixer and mixed for 3-5 minutes. During this period, 0.1-1% of aluminum powder and 0.2-0.9% of silicon powder additives are manually added from the feeding port of the Eirich mixer. After mixing evenly, the reaction section matrix fine powder is obtained. 1-3% of fused magnesia particles (mass ratio of large, medium and small particles is 1:2:1), 4-7% of sintered magnesia particles (mass ratio of large, medium and small particles is 1.2:2:0.8), 30-45% of calcium-containing magnesia particles (mass ratio of large, medium and small particles is 1.1:2:0.9), and 15-25% of forsterite particles (1.05:2:0.95) are transported to a planetary mixer and mixed for 3-5 minutes, then 3.0-3.6% of a phenolic resin binder is added and stirred for 3-5 minutes, 14-18% of low-carbon graphite fine powder is manually added and mixed for 4-5 minutes, and finally the reaction stage matrix fine powder is added and mixed for 3-5 minutes to obtain a reaction stage mixture.

[0030] Middle section: 6-20% of fused magnesia fine powder and 3-7% of sintered magnesia fine powder are transported to the Eirich mixer and mixed for 3-5 minutes. During this period, 0.5-1.5% of aluminum powder and 0.4-1.3% of silicon powder additives are manually added from the Eirich mixer feeding port. After mixing evenly, the middle section matrix fine powder is obtained. 50-60% of fused magnesia particles (mass ratio of large, medium and small particles is 1:2:1) and 10-15% of sintered magnesia particles (mass ratio of large, medium and small particles is 1.2:2:0.8) are transported to a planetary mixer and mixed for 3-5 minutes, then 3.5-4.0% of a phenolic resin binder is added and stirred for 3-5 minutes, and then 11-13% of high-purity graphite fine powder and 3-5% of flake graphite particles (medium particles) are manually added and mixed for 4-5 minutes, and finally the middle-stage matrix fine powder is added and mixed for 3-5 minutes to obtain a middle-stage mixture.

[0031] Back stage: 3-9% of fused magnesia fine powder and 10-18% of sintered magnesia fine powder are transported to the Eirich mixer and mixed for 3-5 minutes. During this period, 0.1-1.0% of aluminum powder and 0.2-0.9% of silicon powder additives are manually added from the Eirich mixer feeding port, and the back stage matrix fine powder is obtained after uniform mixing. 10-15% of fused magnesia particles (large, medium and small particle mass ratio is 1: 2: 1) and 50-60% of sintered magnesia particles (large, medium and small particle mass ratio is 1.2: 2: 0.8) are transported to the planetary mixer and mixed for 3-5 minutes, and then 3.0-3.2% of phenolic resin binder is added and stirred for 3-5 minutes, and then 14-18% of high-purity graphite fine powder is manually added and mixed for 4-5 minutes, and finally the back stage matrix fine powder is added and mixed for 3-5 minutes to obtain the back stage mixture.

[0032] The reaction section, middle section and rear end mixtures are transported to a brick press by belts respectively, and the materials are laid in sequence according to 260±5mm for the reaction section, 350±5mm for the middle section and 350±5mm for the rear section. After that, they are pressurized at two pressure stages: 30-50MPa for 5-10s and 150-200MPa for 5-10s, and then heat treated at 200-250°C for 24-32h to obtain the magnesia carbon bricks for quick change of the converter bottom.

[0033] The fused magnesia has MgO≥97%, SiO2≤0.6%, CaO≤1.5%, and B2O3≤0.01%; particle size: 5-50mm; bulk density: 3.45-3.53g / cm 3 ; True porosity 0.5-2.5%; Grain size 270-700μm.

[0034] The magnesia carbon brick for quick change of converter bottom and its preparation method are characterized in that the sintered magnesia has MgO≥95%, SiO2≤2.2%, CaO≤1.8%; particle size: 5-50mm; bulk density 3.20-3.47g / cm 3 ; True porosity 0.3-3.5%; Grain size 10-200μm.

[0035] The forsterite has MgO+SiO2≥95%, SiO2≥40%, CaO≤1.0%, Al2O3≤1.0%; a particle size of 5-50 mm; and a bulk density of 3.22-3.33 g / cm 3 .

[0036] The calcium-containing magnesium sand has MgO≥90%, CaO of 5-10%, ∑SiO2+Al2O3+Fe2O3≤3.0%; the particle size is 5-50mm; and the bulk density is 3.42-3.47g / cm 3 .

[0037] The jaw crusher has a production capacity of 250-350t / h, a finished product specification of 0-5mm, and a maximum feed particle size of 700mm.

[0038] The production capacity of the double-roll crusher is 50-100t / h, the finished product specification is 0-3mm, and the maximum feed particle size is 60mm.

[0039] The production capacity of the Raymond mill is 10-320t / d, the finished product specification is 0.015-0.088mm, and the maximum feed particle size is 30mm.

[0040] The Eirich mixer model is RV24, and the rotation speed is 0-1751 r / min.

[0041] The planetary mixer has a capacity of 800-1200kg and is equipped with a heating function.

[0042] The aluminum powder has Al≥98%, Fe≤0.5%, Si≤0.5%, and Cu≤0.1%; and a particle size of 0.015-0.074 mm.

[0043] The silicon powder has Si≥98% and a particle size of 0.015-0.074 mm.

[0044] The phenolic resin is in liquid state, with a viscosity of 0.75-0.95 Pa·s at 25° C., a moisture content of 1.5-2.5%, a solid content of 75-80%, a residual carbon rate of 43-48%, a free phenol content of 10.0-12.0%, and a pH value of 6.5-7.5.

[0045] The low-carbon graphite fine powder has a fixed carbon content of 50-80%; the main components of the ash are SiO2, Al2O3 and Fe2O3, and the ∑SiO2+Al2O3+Fe2O3 in the ash is 82.9-88.6%, of which SiO2 accounts for 33-59%; the particle size is 0.044-0.074mm.

[0046] The high-purity graphite fine powder has a fixed carbon content of ≥99.9% and a particle size of 0.074-0.1 mm.

[0047] The flake graphite particles have a fixed carbon content of ≥99.9% and a particle size of 1-3 mm.

[0048] The brick press is a friction brick press with a tonnage of 2500t.

[0049] The present invention is further described below in conjunction with specific implementation modes, but is not intended to limit the protection scope thereof.

[0050] To avoid repetition, the equipment and materials involved in the specific implementation are described as follows, and no further details are given in the embodiments: the fused magnesia has MgO ≥ 97%, SiO2 ≤ 0.6%, CaO ≤ 1.5%, and B2O3 ≤ 0.01%; particle size: 5-50 mm; bulk density 3.45-3.53 g / cm 3 ; True porosity 0.5-2.5%; Grain size 270-700μm.

[0051] The magnesia carbon brick for quick change of converter bottom and its preparation method are characterized in that the sintered magnesia has MgO≥95%, SiO2≤2.2%, CaO≤1.8%; particle size: 5-50mm; bulk density 3.20-3.47g / cm 3 ; True porosity 0.3-3.5%; Grain size 10-200μm.

[0052] The forsterite has MgO+SiO2≥95%, SiO2≥40%, CaO≤1.0%, Al2O3≤1.0%; a particle size of 5-50 mm; and a bulk density of 3.22-3.33 g / cm 3 .

[0053] The magnesia carbon brick for quick change of converter bottom and its preparation method are characterized in that the calcium-containing magnesia sand has MgO≥90%, CaO is 5-10%, ∑SiO2+Al2O3+Fe2O3≤3.0%; the particle size is 5-50mm; the volume density is 3.42-3.47g / cm 3 .

[0054] The jaw crusher has a production capacity of 250-350t / h, a finished product specification of 0-5mm, and a maximum feed particle size of 700mm.

[0055] The production capacity of the double-roll crusher is 50-100t / h, the finished product specification is 0-3mm, and the maximum feed particle size is 60mm.

[0056] The production capacity of the Raymond mill is 10-320t / d, the finished product specification is 0.015-0.088mm, and the maximum feed particle size is 30mm.

[0057] The Eirich mixer model is RV24, and the rotation speed is 0-1751 r / min.

[0058] The planetary mixer has a capacity of 800-1200kg and is equipped with a heating function.

[0059] The aluminum powder has Al≥98%, Fe≤0.5%, Si≤0.5%, and Cu≤0.1%; and a particle size of 0.015-0.074 mm.

[0060] The silicon powder has Si≥98% and a particle size of 0.015-0.074 mm.

[0061] The phenolic resin is in liquid state, with a viscosity of 0.75-0.95 Pa·s at 25° C., a moisture content of 1.5-2.5%, a solid content of 75-80%, a residual carbon rate of 43-48%, a free phenol content of 10.0-12.0%, and a pH value of 6.5-7.5.

[0062] The low-carbon graphite fine powder has a fixed carbon content of 50-80%; the main components of the ash are SiO2, Al2O3 and Fe2O3, and the ∑SiO2+Al2O3+Fe2O3 in the ash is 82.9-88.6%, of which SiO2 accounts for 33-59%; the particle size is 0.044-0.074mm.

[0063] The high-purity graphite fine powder has a fixed carbon content of ≥99.9% and a particle size of 0.074-0.1 mm.

[0064] The flake graphite particles have a fixed carbon content of ≥99.9% and a particle size of 1-3 mm.

[0065] The brick press is a friction brick press with a tonnage of 2500t. Example 1 (Replace all)

[0066] A magnesia carbon brick for quick replacement of converter bottom and its preparation method. This embodiment will completely replace the original bricks of the converter bottom, and the steps of the preparation method are: Step 1 (aggregate preparation): 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed by jaw crusher and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles in turn; to ensure the balance of the material block surface, part of 1-3mm or 3-5mm can be crushed into 0.1-1mm or 1-3mm by roller crusher. The crushed particles are stored in the corresponding silo according to the particle size.

[0067] 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles.

[0068] Step 2 (preparation of matrix fine powder): After the silo stores a sufficient amount of the particles, stop storing. Next, the particles that have passed through the jaw crusher are directly sent to the Raymond mill to form the matrix fine powder (fused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, calcium-containing magnesia fine powder) with a particle size of less than 0.088 mm after powdering, and stored in the corresponding silo.

[0069] In actual production, step one and step two can be performed simultaneously to shorten the preparation time of aggregate and matrix.

[0070] Step 3 (mixing and molding): Use a computer to control the transport cart to transport the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer. The mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt.

[0071] The magnesia-carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860 mm, which are divided into a reaction section (260±10 mm), a middle section (350±10 mm) and a rear section (350±10 mm).

[0072] Reaction section: 5% of fused magnesia fine powder, 8% of sintered magnesia fine powder, 10% of calcium-containing magnesia fine powder and 4% of forsterite fine powder were transported to the Eirich mixer and mixed for 3 minutes. During this period, 0.1% of aluminum powder and 0.2% of silicon powder additives were manually added from the feeding port of the Eirich mixer. After mixing evenly, the reaction section matrix fine powder was obtained. 3% of fused magnesia particles (mass ratio of large, medium and small particles is 1:2:1), 7% of sintered magnesia particles (mass ratio of large, medium and small particles is 1.2:2:0.8), 30% of calcium-containing magnesia particles (mass ratio of large, medium and small particles is 1.1:2:0.9), and 15% of forsterite particles (1.05:2:0.95) are transported to a planetary mixer and mixed for 3 minutes, then 3.6% of a phenolic resin binder is added and stirred for 3 minutes, and then 18% of low-carbon graphite fine powder is manually added and mixed for 4 minutes, and finally the reaction stage matrix fine powder is added and mixed for 3 minutes to obtain a reaction stage mixture.

[0073] Middle section: 16% of fused magnesia fine powder and 3% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 3 minutes. During this period, 0.5% of aluminum powder and 0.4% of silicon powder additives were added from the Eirich mixer feeding port manually, and the middle section matrix fine powder was obtained after uniform mixing. 55% of fused magnesia particles (large, medium and small particle mass ratio was 1:2:1) and 10% of sintered magnesia particles (large, medium and small particle mass ratio was 1.2:2:0.8) were transported to the planetary mixer and mixed for 3 minutes, and then 4.0% of phenolic resin binder was added and stirred for 3 minutes, and then 11% of high-purity graphite fine powder and 5% of flake graphite particles (medium particles) were added manually and mixed for 4 minutes, and finally the middle section matrix fine powder was added and mixed for 3 minutes to obtain the middle section mixture.

[0074] Back stage: 5% of fused magnesia fine powder and 10% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 3 minutes. During this period, 0.1% of aluminum powder and 0.9% of silicon powder additives were added from the Eirich mixer feeding port manually, and the back stage matrix fine powder was obtained after uniform mixing. 11% of fused magnesia particles (large, medium and small particle mass ratio was 1:2:1) and 59% of sintered magnesia particles (large, medium and small particle mass ratio was 1.2:2:0.8) were transported to the planetary mixer and mixed for 3 minutes, and then 3.0% of phenolic resin binder was added and stirred for 3 minutes, and then 15% of high-purity graphite fine powder was added manually and mixed for 4 minutes, and finally the back stage matrix fine powder was added and mixed for 3 minutes to obtain the back stage mixture.

[0075] The reaction section, middle section and rear end mixtures are transported to the brick press by belts respectively, and the materials are laid in order of 260mm for the reaction section, 350mm for the middle section and 350mm for the rear section. After that, they are pressurized at 30MPa for 7s and 150MPa for 10s, and then heat treated at 200°C for 32h to obtain the magnesia carbon bricks for quick change of the converter bottom.

[0076] The magnesia-carbon bricks for quick change of converter bottom prepared in this embodiment were tested: special steel was smelted after 5 furnaces; after 1000 furnaces, the thickness of the furnace bottom increased significantly, affecting the bottom blowing effect of the converter. Example 2 (Replacing air-permeable bricks)

[0077] A magnesia carbon brick for quick replacement of converter bottom and a preparation method thereof. This embodiment only replaces the air permeable bricks at the bottom of the converter, and the steps of the preparation method are: Step 1 (aggregate preparation): 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed by jaw crusher and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles in turn; to ensure the balance of the material block surface, part of 1-3mm or 3-5mm can be crushed into 0.1-1mm or 1-3mm by roller crusher. The crushed particles are stored in the corresponding silo according to the particle size.

[0078] 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles.

[0079] Step 2 (preparation of matrix fine powder): After the silo stores a sufficient amount of the particles, stop storing. Next, the particles that have passed through the jaw crusher are directly sent to the Raymond mill to form the matrix fine powder (fused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, calcium-containing magnesia fine powder) with a particle size of less than 0.088 mm after powdering, and stored in the corresponding silo.

[0080] In actual production, step one and step two can be performed simultaneously to shorten the preparation time of aggregate and matrix.

[0081] Step 3 (mixing and molding): Use a computer to control the transport cart to transport the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer. The mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt.

[0082] The magnesia-carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860 mm, which are divided into a reaction section (260±10 mm), a middle section (350±10 mm) and a rear section (350±10 mm).

[0083] Reaction section: 3% of fused magnesia fine powder, 3% of sintered magnesia fine powder, 12% of calcium-containing magnesia fine powder, and 8% of forsterite fine powder were transported to the Eirich mixer and mixed for 3 minutes. During this period, 1% of aluminum powder and 0.9% of silicon powder additives were manually added from the feeding port of the Eirich mixer. After mixing evenly, the reaction section matrix fine powder was obtained. 1% of fused magnesia particles (mass ratio of large, medium and small particles is 1:2:1), 4% of sintered magnesia particles (mass ratio of large, medium and small particles is 1.2:2:0.8), 30% of calcium-containing magnesia particles (mass ratio of large, medium and small particles is 1.1:2:0.9), and 25% of forsterite particles (1.05:2:0.95) are transported to a planetary mixer and mixed for 3 minutes, then 3.0% of a phenolic resin binder is added and stirred for 3 minutes, and then 14% of low-carbon graphite fine powder is manually added and mixed for 4 minutes, and finally the reaction stage matrix fine powder is added and mixed for 3 minutes to obtain a reaction stage mixture.

[0084] Middle section: 14% of fused magnesia fine powder and 7% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 4 minutes. During this period, 1.5% of aluminum powder and 1.3% of silicon powder additives were added from the Eirich mixer feeding port manually, and the middle section matrix fine powder was obtained after uniform mixing. 50% of fused magnesia particles (mass ratio of large, medium and small particles was 1:2:1) and 15% of sintered magnesia particles (mass ratio of large, medium and small particles was 1.2:2:0.8) were transported to the planetary mixer and mixed for 4 minutes, and then 3.5% of phenolic resin binder was added and stirred for 4 minutes, and then 11% of high-purity graphite fine powder and 3% of flake graphite particles (medium particles) were added manually and mixed for 4 minutes, and finally the middle section matrix fine powder was added and mixed for 4 minutes to obtain the middle section mixture.

[0085] Back stage: 6% of fused magnesia fine powder and 10% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 3 minutes. During this period, 1.0% of aluminum powder and 0.2% of silicon powder additives were added from the Eirich mixer feeding port manually, and the back stage matrix fine powder was obtained after uniform mixing. 14% of fused magnesia particles (large, medium and small particle mass ratio was 1:2:1) and 56% of sintered magnesia particles (large, medium and small particle mass ratio was 1.2:2:0.8) were transported to the planetary mixer and mixed for 3 minutes, and then 3.1% of phenolic resin binder was added and stirred for 4 minutes, and then 14% of high-purity graphite fine powder was added manually and mixed for 4 minutes, and finally the back stage matrix fine powder was added and mixed for 3 minutes to obtain the back stage mixture.

[0086] The reaction section, middle section and rear end mixtures are transported to the brick press by belts respectively, and the materials are laid in order of 260mm for the reaction section, 350mm for the middle section and 350mm for the rear section. After that, they are pressurized at 40MPa for 6s and 150MPa for 5s and then heat treated at 220°C for 30h to obtain the magnesia carbon bricks for quick change of the converter bottom.

[0087] The magnesia-carbon bricks for quick change of converter bottom prepared in this embodiment were tested: special steel was smelted after the 5th furnace; at the 26th furnace, the air pipe bricks were damaged and the surrounding refractory bricks were also damaged. Example 3 (Replacing the air-permeable bricks and the surrounding 5 layers of refractory bricks)

[0088] A magnesia carbon brick for quick replacement of converter bottom and a preparation method thereof. This embodiment replaces the air permeable bricks at the bottom of the converter and the surrounding five layers of refractory bricks. The steps of the preparation method are: Step 1 (aggregate preparation): 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed by jaw crusher and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles in turn; to ensure the balance of the material block surface, part of 1-3mm or 3-5mm can be crushed into 0.1-1mm or 1-3mm by roller crusher. The crushed particles are stored in the corresponding silo according to the particle size.

[0089] 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles.

[0090] Step 2 (preparation of matrix fine powder): After the silo stores a sufficient amount of the particles, stop storing. Next, the particles that have passed through the jaw crusher are directly sent to the Raymond mill to form the matrix fine powder (fused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, calcium-containing magnesia fine powder) with a particle size of less than 0.088 mm after powdering, and stored in the corresponding silo.

[0091] In actual production, step one and step two can be performed simultaneously to shorten the preparation time of aggregate and matrix.

[0092] Step 3 (mixing and molding): Use a computer to control the transport cart to transport the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer. The mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt.

[0093] The magnesia-carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860 mm, which are divided into a reaction section (260±10 mm), a middle section (350±10 mm) and a rear section (350±10 mm).

[0094] Reaction section: 4% of fused magnesia fine powder, 5% of sintered magnesia fine powder, 12% of calcium-containing magnesia fine powder, and 6% of forsterite fine powder were transported to the Eirich mixer and mixed for 3 minutes. During this period, 0.5% of aluminum powder and 0.5% of silicon powder additives were manually added from the feeding port of the Eirich mixer. After mixing evenly, the reaction section matrix fine powder was obtained. 2% of fused magnesia particles (mass ratio of large, medium and small particles is 1:2:1), 5% of sintered magnesia particles (mass ratio of large, medium and small particles is 1.2:2:0.8), 35% of calcium-containing magnesia particles (mass ratio of large, medium and small particles is 1.1:2:0.9), and 15% of forsterite particles (1.05:2:0.95) are transported to a planetary mixer and mixed for 3 minutes, then 3.4% of a phenolic resin binder is added and stirred for 4 minutes, and then 16% of low-carbon graphite fine powder is manually added and mixed for 5 minutes, and finally the reaction stage matrix fine powder is added and mixed for 4 minutes to obtain a reaction stage mixture.

[0095] Middle section: 9% of fused magnesia fine powder and 7% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 5 minutes. During this period, 1.0% of aluminum powder and 1.0% of silicon powder additives were added from the Eirich mixer feeding port manually, and the middle section matrix fine powder was obtained after uniform mixing. 60% of fused magnesia particles (large, medium and small particle mass ratio was 1:2:1) and 10% of sintered magnesia particles (large, medium and small particle mass ratio was 1.2:2:0.8) were transported to the planetary mixer and mixed for 5 minutes, and then 4.0% of phenolic resin binder was added and stirred for 5 minutes, and then 11% of high-purity graphite fine powder and 3% of flake graphite particles (medium particles) were added manually and mixed for 5 minutes, and finally the middle section matrix fine powder was added and mixed for 5 minutes to obtain the middle section mixture.

[0096] Back stage: 4% of fused magnesia fine powder and 18% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 4 minutes. During this period, 0.5% of aluminum powder and 0.8% of silicon powder additives were added from the Eirich mixer feeding port manually, and the back stage matrix fine powder was obtained after uniform mixing. 10% of fused magnesia particles (mass ratio of large, medium and small particles was 1:2:1) and 50% of sintered magnesia particles (mass ratio of large, medium and small particles was 1.2:2:0.8) were transported to a planetary mixer and mixed for 4 minutes, and then 3.1% of phenolic resin binder was added and stirred for 5 minutes, and then 18% of high-purity graphite fine powder was added manually and mixed for 5 minutes, and finally the back stage matrix fine powder was added and mixed for 4 minutes to obtain the back stage mixture.

[0097] The reaction section, middle section and rear end mixtures are transported to the brick press by belts respectively, and the materials are laid in order of 260mm for the reaction section, 350mm for the middle section and 350mm for the rear section. After that, they are pressurized at 50MPa for 5s and 200MPa for 5s, and then heat treated at 230°C for 26h to obtain the magnesia carbon bricks for quick change of the converter bottom.

[0098] The magnesia carbon bricks for quick change of converter bottom prepared in this embodiment were tested: special steel was smelted after the 5th furnace; the furnace age was 8541 furnace, 8695 furnace, and 9021 furnace. In the early stage, the slag-metal mushroom head structure could be formed, but bottom blowing was occasionally blocked in the early stage, and the bottom blowing gas flow rate decreased. Example 4 (Replace 5 layers of refractory bricks around the air-permeable bricks, do not replace the air-permeable bricks)

[0099] A magnesia carbon brick for quick replacement of converter bottom and a preparation method thereof. In this embodiment, five layers of refractory bricks around the permeable bricks at the bottom of the converter are replaced without replacing the permeable bricks. The steps of the preparation method are: Step 1 (aggregate preparation): 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed by jaw crusher and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles in turn; to ensure the balance of the material block surface, part of 1-3mm or 3-5mm can be crushed into 0.1-1mm or 1-3mm by roller crusher. The crushed particles are stored in the corresponding silo according to the particle size.

[0100] 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles.

[0101] Step 2 (preparation of matrix fine powder): After the silo stores a sufficient amount of the particles, stop storing. Next, the particles that have passed through the jaw crusher are directly sent to the Raymond mill to form the matrix fine powder (fused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, calcium-containing magnesia fine powder) with a particle size of less than 0.088 mm after powdering, and stored in the corresponding silo.

[0102] In actual production, step one and step two can be performed simultaneously to shorten the preparation time of aggregate and matrix.

[0103] Step 3 (mixing and molding): Use a computer to control the transport cart to transport the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer. The mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt.

[0104] The magnesia-carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860 mm, which are divided into a reaction section (260±10 mm), a middle section (350±10 mm) and a rear section (350±10 mm).

[0105] Reaction section: 3% of fused magnesia fine powder, 4% of sintered magnesia fine powder, 15% of calcium-containing magnesia fine powder, and 8% of forsterite fine powder were transported to the Eirich mixer and mixed for 5 minutes. During this period, 0.5% of aluminum powder and 0.6% of silicon powder additives were manually added from the feeding port of the Eirich mixer. After mixing evenly, the reaction section matrix fine powder was obtained. 1% of fused magnesia particles (mass ratio of large, medium and small particles is 1:2:1), 4% of sintered magnesia particles (mass ratio of large, medium and small particles is 1.2:2:0.8), 30% of calcium-containing magnesia particles (mass ratio of large, medium and small particles is 1.1:2:0.9), and 20% of forsterite particles (1.05:2:0.95) are transported to a planetary mixer and mixed for 5 minutes, then 3.2% of a phenolic resin binder is added and stirred for 5 minutes, 15% of low-carbon graphite fine powder is manually added and mixed for 5 minutes, and finally the reaction stage matrix fine powder is added and mixed for 5 minutes to obtain a reaction stage mixture.

[0106] Middle section: 20% of fused magnesia fine powder and 3% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 5 minutes. During this period, 1.2% of aluminum powder and 1.0% of silicon powder additives were added from the Eirich mixer feeding port manually, and the middle section matrix fine powder was obtained after uniform mixing. 50% of fused magnesia particles (large, medium and small particle mass ratio was 1:2:1) and 11% of sintered magnesia particles (large, medium and small particle mass ratio was 1.2:2:0.8) were transported to the planetary mixer and mixed for 5 minutes, and then 3.5% of phenolic resin binder was added and stirred for 5 minutes, and then 13% of high-purity graphite fine powder and 3% of flake graphite particles (medium particles) were added manually and mixed for 5 minutes, and finally the middle section matrix fine powder was added and mixed for 5 minutes to obtain the middle section mixture.

[0107] Back stage: 5% of fused magnesia fine powder and 18% of sintered magnesia fine powder were transported to the Eirich mixer and mixed for 5 minutes. During this period, 1.0% of aluminum powder and 0.9% of silicon powder additives were added from the Eirich mixer feeding port manually, and the back stage matrix fine powder was obtained after uniform mixing. 10% of fused magnesia particles (mass ratio of large, medium and small particles was 1:2:1) and 53% of sintered magnesia particles (mass ratio of large, medium and small particles was 1.2:2:0.8) were transported to a planetary mixer and mixed for 5 minutes, and then 3.2% of phenolic resin binder was added and stirred for 5 minutes, and then 14% of high-purity graphite fine powder was added manually and mixed for 5 minutes, and finally the back stage matrix fine powder was added and mixed for 5 minutes to obtain the back stage mixture.

[0108] The reaction section, middle section and rear end mixtures are transported to the brick press by belts respectively, and the materials are laid in order of 260mm for the reaction section, 350mm for the middle section and 350mm for the rear section. After that, they are pressurized at 50MPa for 10s and 200MPa for 10s, and then heat treated at 250°C for 24h to obtain the magnesia carbon bricks for quick change of the converter bottom.

[0109] The magnesia-carbon bricks for quick replacement of the converter bottom prepared in this embodiment were tested: special steel was smelted after the 5th furnace; the furnace age was 8368-9568 furnaces, and there was no thickening of the furnace bottom around 1000 furnaces. The early slag-metal mushroom head structure was stable, and the bottom blowing gas flow was stable.

[0110] The above description is only a specific embodiment of the present invention, but the structural features of the protection scope of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.

Claims

1. A magnesia carbon brick for quick change of converter bottom and its preparation method, characterized in that: The following steps are involved: Step 1: Preparation of aggregate: 5-50mm fused magnesia, sintered magnesia, forsterite, and calcium-containing magnesia are crushed by jaw crusher in turn and sieved into 0.1-1mm, 1-3mm, and 3-5mm particles; to maintain material balance, 10-70% of 1-3mm or 3-5mm are crushed into 0.1-1mm or 1-3mm by roller crusher; the crushed particles are stored in corresponding silos according to particle size; 0.1-1mm is called small particles, 1-3mm is called medium particles, and 3-5mm is called large particles; Step 2: Preparation of matrix fine powder: After the silo stores 5-12 tons of particles from step 1, stop storing, and then directly send the particles that have passed through the jaw crusher into the Raymond mill. After the powder is crushed, matrix fine powder with a particle size of less than 0.088 mm is formed, namely, fused magnesia fine powder, sintered magnesia fine powder, forsterite fine powder, and calcium-containing magnesia fine powder, and stored in the corresponding silo; in actual production, step 1 and step 2 can be carried out simultaneously to shorten the preparation time of aggregate and matrix; Step 3: Mixing and forming: The transport cart transports the above particles from each silo to the planetary mixer and the fine powder to the Eirich mixer. The mixed matrix fine powder is transported to the planetary mixer by a belt, and the mixture is transported to the brick press by a belt. The magnesia carbon bricks for quick change of the converter bottom are gradient refractory materials with a total length of 860±30mm, which are divided into a reaction section of 260±10mm, a middle section of 350±10mm and a rear section of 350±10mm. Reaction section: 3-5% fused magnesia fine powder, 3-8% sintered magnesia fine powder, 10-15% calcium-containing magnesia fine powder, and 4-8% forsterite fine powder are transported to the Eirich mixer and mixed for 3-5 minutes. During this period, 0.1-1% aluminum powder and 0.2-0.9% silicon powder additives are manually added from the Eirich mixer feeding port. After mixing evenly, the reaction section matrix fine powder is obtained. 1-3% fused magnesia particles with a mass ratio of large, medium and small particles of 1:2:1, 4-7% large, medium and small particles with a mass ratio of 1.2:2:0.8 are added. Sintered magnesia particles, 30-45% calcium-containing magnesia particles with a mass ratio of large, medium and small particles of 1.1:2:0.9, and 15-25% forsterite particles with a mass ratio of large, medium and small particles of 1.05:2:0.95 are transported to a planetary mixer and mixed for 3-5 minutes, then 3.0-3.6% phenolic resin binder is added and stirred for 3-5 minutes, and then 14-18% low-carbon graphite fine powder is manually added and mixed for 4-5 minutes, and finally the reaction stage matrix fine powder is added and mixed for 3-5 minutes to obtain a reaction stage mixture; Middle section: 6-20% of fused magnesia fine powder and 3-7% of sintered magnesia fine powder are transported to the Eirich mixer and mixed for 3-5 minutes. During this period, 0.5-1.5% of aluminum powder and 0.4-1.3% of silicon powder additives are manually added from the feeding port of the Eirich mixer. After mixing evenly, the middle section matrix fine powder is obtained; 50-60% of fused magnesia particles with a mass ratio of large, medium and small particles of 1:2:1 and 10-15% of sintered magnesia particles with a mass ratio of large, medium and small particles of 1.2:2:0.8 are transported to the planetary mixer Mix for 3-5 minutes, then add 3.5-4.0% phenolic resin binder and stir for 3-5 minutes, then add 11-13% high-purity graphite fine powder and 3-5% flake graphite medium particles and mix for 4-5 minutes, and finally add the middle stage matrix fine powder and mix for 3-5 minutes to obtain the middle stage mixture; the latter stage: 3-9% fused magnesia fine powder and 10-18% sintered magnesia fine powder are transported to the Eirich mixer and mixed for 3-5 minutes, during which 0.0 ... .1-1.0% aluminum powder and 0.2-0.9% silicon powder additives are mixed evenly to obtain the rear-stage matrix fine powder; 10-15% fused magnesia particles with a mass ratio of large, medium and small particles of 1:2:1 and 50-60% sintered magnesia particles with a mass ratio of large, medium and small particles of 1.2:2:0.8 are transported to a planetary mixer and mixed for 3-5 minutes, then 3.0-3.2% phenolic resin binder is added and stirred for 3-5 minutes, and then 14-18% high-purity graphite fine powder is added manually and mixed for 4-5 minutes. in, and finally add the rear-stage matrix fine powder and mix for 3-5 minutes to obtain the rear-stage mixture; the reaction section, middle section and rear-end mixtures are respectively transported to the brick press by belts, and the materials are laid in the reaction section at 260±5mm, the middle section at 350±5mm and the rear section at 350±5mm in sequence, and then pressurized at two stages of 30-50MPa for 5-10s and 150-200MPa for 5-10s, and then heat treated at 200-250℃ for 24-32h to obtain the magnesia-carbon bricks for quick replacement of the converter bottom.

2. The magnesia carbon brick for quick change of converter bottom and its preparation method according to claim 1, characterized in that: The fused magnesia has MgO≥97%, SiO2≤0.6%, CaO≤1.5%, B2O3≤0.01%, particle size: 5-50mm; bulk density 3.45-3.53g / cm 3 , true porosity 0.5-2.5%, grain size 270-700μm; the sintered magnesia MgO≥95%, SiO2≤2.2%, CaO≤1.8%, particle size: 5-50mm, volume density 3.20-3.47g / cm 3 , true porosity 0.3-3.5%, grain size 10-200μm; the forsterite MgO+SiO2≥95%, SiO2≥40%, CaO≤1.0%, Al2O3≤1.0%, particle size 5-50mm, volume density 3.22-3.33g / cm 3 The calcium-containing magnesia sand has MgO≥90%, CaO is 5-10%, ∑SiO2+Al2O3+Fe2O3≤3.0%, a particle size of 5-50mm, and a bulk density of 3.42-3.47g / cm 3 .

3. The magnesia carbon brick for quick change of converter bottom and its preparation method according to claim 1, characterized in that: The production capacity of the jaw crusher is 250-350t / h, the finished product specification is 0-5mm, and the maximum feed particle size is 700mm; the production capacity of the double-roll crusher is 50-100t / h, the finished product specification is 0-3mm, and the maximum feed particle size is 60mm; the production capacity of the Raymond mill is 10-320t / d, the finished product specification is 0.015-0.088mm, and the maximum feed particle size is 30mm; the model of the Eirich mixer is RV24, and the speed is 0-1751r / min; the capacity of the planetary mixer is 800-1200kg, and it has a heating function.

4. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The aluminum powder has Al≥98%, Fe≤0.5%, Si≤0.5%, Cu≤0.1%, and a particle size of 0.015-0.074 mm; the silicon powder has Si≥98%, and a particle size of 0.015-0.074 mm.

5. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The phenolic resin is in liquid state, with a viscosity of 0.75-0.95 Pa·s at 25° C., a moisture content of 1.5-2.5%, a solid content of 75-80%, a residual carbon rate of 43-48%, a free phenol content of 10.0-12.0%, and a pH value of 6.5-7.

5.

6. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The low-carbon graphite fine powder has a fixed carbon content of 50-80%; the main components of the ash are SiO2, Al2O3 and Fe2O3, and the ∑SiO2+Al2O3+Fe2O3 in the ash is 82.9-88.6%, of which SiO2 accounts for 33-59%, and the particle size is 0.044-0.074mm.

7. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The high-purity graphite fine powder has a fixed carbon content of ≥99.9% and a particle size of 0.074-0.1 mm.

8. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The flake graphite particles have a fixed carbon content of ≥99.9% and a particle size of 1-3 mm.

9. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The brick press is a friction brick press.

10. The magnesia carbon brick for quick change of converter bottom and the preparation method thereof according to claim 1, characterized in that: The magnesia-carbon brick for quick replacement of the converter bottom is a magnesia-carbon brick for quick replacement of the converter bottom prepared by the method for preparing magnesia-carbon brick for quick replacement of the converter bottom according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for replacing converter bottom blowing seat brick

    CN110184412A

  • Preparation process of magnesia carbon brick for tapping hole of converter

    CN117430407A

  • Dry type magnesium-calcium gravity flow fire-resistant material and preparation thereof

    CN101462887A

  • Magnesia carbon brick taking composite magnesia as major raw material and preparation method thereof

    CN102093065A

  • Converter repairing mass and preparation method thereof

    CN105801136A